2018
DOI: 10.1155/2018/6329531
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Design of a Metamaterial Lens Antenna Using the Theory of Characteristic Modes

Abstract: A new single-layer metamaterial lens antenna aimed to operate at 10 GHz is proposed in this paper. The lens antenna consists of twelve capacitively coupled unit cells distributed along a ring and illuminated by an open-ended circular waveguide with a metallic resonant ring. The theory of characteristic modes is used to analyze the metamaterial lens, in order to provide an insight into the radiation characteristics of the antenna. The proposed antenna has been optimized, obtaining a large bandwidth and a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…The resonance frequencies of TM 10 and TM 20 modes are indicated by the intersection points of the dispersion curves and the vertical lines which correspond to 180/πβP x = 53°and 180/πβP y = 77°, respectively, as shown in Figure 8. We can see that the predicted resonances for TM 10 and TM 20 (corresponding 4.62 and 5.61 GHz) are very close to the simulated first and second resonant frequencies (4.83 and 5.48 GHz) of the PSMS antenna. In brief, the dispersion analysis discussed above demonstrated that the radiation mechanism of the proposed antenna can be pretty good explained by transmission-line model.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…The resonance frequencies of TM 10 and TM 20 modes are indicated by the intersection points of the dispersion curves and the vertical lines which correspond to 180/πβP x = 53°and 180/πβP y = 77°, respectively, as shown in Figure 8. We can see that the predicted resonances for TM 10 and TM 20 (corresponding 4.62 and 5.61 GHz) are very close to the simulated first and second resonant frequencies (4.83 and 5.48 GHz) of the PSMS antenna. In brief, the dispersion analysis discussed above demonstrated that the radiation mechanism of the proposed antenna can be pretty good explained by transmission-line model.…”
supporting
confidence: 71%
“…MSs can be divided into several types, including electromagnetic band-gap (EBGs) structures, reactive impedance surfaces (RISs), and high impedance surfaces (HISs) or artificial magnetic conductors (AMCs) [5][6][7][8]. Owing to their exotic electromagnetic properties, MSs have been widely applied in the design of microwave absorbers, thin planar lens, filters, and so on [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TCM is based on the method of moment formulation of electric field integral equation and is found to be useful in proving various antenna parameters in the literature. In recent years, different types of antennas well designed by using characteristic mode theory (CMT) for different applications are Slot antennas [7][8][9][10], MIMO antennas [11][12][13][14], UWB antennas [15][16][17], Platform antennas [18][19][20][21], Metasurface antennas [22][23][24][25][26], and Wideband antennas [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…For more than a decade, the TCM has been used to design mobile antennas [13], analyze slotted planar structures [14,15], study some canonical structures such as spheres or cylinders [16], design wideband omnidirectional antennas [17], or provide design guidelines for open slot antennas embedded in finite platforms [18]. The TCM has also been used to analyze metallic lenses, such as a lens formed by twelve metallic rings distributed in a single-layer in [19], a low-profile lens made of metallic cylinders [20], or a metallic lens designed with a central circular metallic ring surrounded by a set of eight metallic rings.…”
Section: Introductionmentioning
confidence: 99%